Time-Delayed Tandem Microwave Observations of Tropical Deep Convection: Overview of the C2OMODO Mission - Brogniez, Hélène; Roca, Rémy; Auguste, Franck; Chaboureau, Jean-Pierre; Haddad, Ziad; Munchak, Stephen J.; Li, Xiaowen; Bouniol, Dominique; Dépée, Alexis; Fiolleau, Thomas; Kollias, Pavlos (Frontiers in Remote Sensing, 2022)
Convective clouds serve as a primary mechanism for the transfer of thermal energy, moisture, and momentum through the troposphere. Arguably, satellite observations are the only viable way to sample the convective updrafts over the oceans. Here, the potential of temporal derivatives of measurements performed in H2O lines (183GHz and 325GHz) to infer the deep convective vertical air motions is assessed. High-resolution simulations of tropical convection are combined to radiative transfer models to explore the information content of time-derivative maps (as short as 30 s) of brightness temperatures (dTb/dt). The 183-GHz Tb signal from hydrometeors is used to detect the location of convective cores. The forward simulations suggest that within growing convective cores, the dTb/dt is related to the vertically integrated ice mass flux and that it is sensitive to the temporal evolution of microphysical properties along the life cycle of convection. In addition, the area-integrated dTb/dt, is related to the amount, size, and density of detrained ice, which are controlled by riming and aggregation process rates. These observations, particularly in conjunction with Doppler velocity measurements, can be used to refine these assumptions in ice microphysics parameterizations. Further analyses show that a spectral sampling of the 183GHz absorbing line can be used to estimate the maximum in-cloud vertical velocity that is reached as well as its altitude with reasonable uncertainties.